Comparative efficacy of sports massage and foam rolling on muscle performance in university-level futsal athletes / Nur Afrina Batrisyia Mahadi ... [et al.]. - Mahadi, Nur Afrina Batrisyia; Raja Hussein, Raja Nurul Jannat; Saiful Annur, Muhamad Safiq; Adnan, Muhamad Aizzat; Shaari, Maisharah; Mazaulan, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the effects of sport massage (SM) and foam rolling (FR) on muscle performance among UiTM Negeri Sembilan futsal players. Despite their growing popularity, evidence on their effectiveness in improving strength, power, and endurance remains inconsistent. By comparing these interventions, this research seeks to clarify their impact and provide practical insights for optimizing athletic training and recovery strategies [1]. A quasi-experimental design involving 10 randomly selected UiTM Negeri Sembilan futsal players aged 18–25 was employed. Participants met strict inclusion criteria, ensuring active training history and no recent injuries. Muscle performance was assessed using the broad jump and agility T-test before, immediately and 72 hours after 9o minutes training with 80% intensity. This approach provided reliable data to evaluate the comparative effects of 15 minutes of SM and 15 minutes of foam rolling on power, and agility.